(untitled) (Mugda Medical College Journal, 2022)
Background: It is known that individuals with autoimmune diseases such as pemphigus vulgaris (PV) are at increased risk of developing other autoimmune diseases. However, it is not clearly known whether there is any specific relationship between PV and thyroid autoimmunity. Objective: The study aims to determine the effects of pemphigus vulgaris on the thyroid glands with analyzing the thyroid function tests. Methods: This cross-sectional, descriptive study was conducted in the Department of Dermatology & Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between November 2015 and October 2016. A total of 42 patients participated in this study. Pemphigus vulgaris was diagnosed clinically with the help of a panel of experts and confirmed by the investigations e.g., histopathological and DIF examination. Demographic profile, detailed history, and clinical features was recorded in data collection sheet. Then the thyroid function tests – serum TSH, FT4, and FT3 were measured by chemiluminescent microparticle immunoassay. Results: In the present study, the mean age of the patients was 46.7±9.9 years. Male: female ratio was 1.1:1. Hypertension was the most commonly observed comorbidity (16.7%), followed by anaemia (11.9%). Seum TSH was abnormal in 9.5% patients, while abnormal serum FT4 was observed in 2.4%, and FT3 in 16.7%. Overall, most of the patients (88.1%) had normal thyroid functions i.e., euthyroid state, 4(9.5%) patients had hypothyroidism and 1(2.4%) had hyperthyroid state. Conclusion: Among pemphigus vulgaris patients, thyroid function tests revealed that serum FT3 is the most affected by pemphigus vulgaris; nonetheless, serum TSH and FT4 are also affected in smaller proportion in comparison to FT3. Mugda Med Coll J. 2022; 5(1): 29-33